Sistem pakar untuk Mendeteksi Kerusakan Forklift Menggunakan Forward Chaining - Sinaga, Rini Suriani; Saragih, Saut Pintubipar (LPPM Universitas Putera Batam, 2020)
A forklift is a lift aircraft that functions to move, lower and lift goods from different heights that may not be accessible to humans. In the operation of a forklift if given load will definitely experience fatigue so that the machine will break down at any time. The problem that occurs is that many forklift operators cannot repair a forklift used when experiencing problems. Many forklift operators who do not know about the sign of damage. So that when the damage is minor, it can still be repaired by itself, but if the damage is already severe, at least the operator knows which parts are damaged and can be protected from fraud by irresponsible workshop mechanics. Expert system is one branch of artificial intelligence that defines how to move the ability of an expert in thinking and reasoning in solving problems and making decisions and conclusions from a number of facts.The method used in this research is forward chaining. In this method, the data is used to determine which rules will be run, then the rules will be run. It is used for the process of adding data to working memory. The process is then repeated until a result is found.